The Influence of Job Autonomy on Intention to Stay among Academics Employed at Malaysian Research Universities: The Mediating Role of Employee Engagement - Ong, Yean Sze; Abdul Rahim, Noor Fareen; Hanifah, Haniruzila Md.; Jauhar, Junaimah (Journal of Entrepreneurship, Business and Economics, 2023)
The purpose of this paper is to examine the influence of job autonomy on the intention to stay among Malaysian academics in the context of Malaysian research universities. A model was developed based on the self-determination theory to identify how job autonomy can enhance the intention to stay through employee engagement. Data was collected from 329 Malaysian academics from five Malaysian research universities via an online survey questionnaire. The collected data was then analyzed using Smart PLS. Findings indicate that job autonomy has a significant positive impact on employee engagement. Employee engagement also has a significant positive relationship with the intention to stay. Furthermore, job autonomy was also found to have a significant indirect effect on the intention to stay via employee engagement as a mediator. The theoretical contribution of this paper contributes to developing an understanding of the linkage between job autonomy and intention to stay as well as providing insight about the mediation of employee engagement, highlighting the novelty of this conceptual framework. This study also makes significant practical contributions to both academics and policy makers on the vital roles of job autonomy and employee engagement, thus enhancing the intention to stay among academics. Finally, the limitations of the study were explained and recommendations for future research were also presented. Research paper Keywords: Job autonomy; Employee Engagement; Intention to stay; Self-Determination Theory; Malaysian Research Universities Reference to this paper should be made as follows: Ong, Y. S., Rahim, N. F. A., Hanifah, H. M., & Jauhar, J. (2023). The Influence of Job Autonomy on Intention to Stay among Academics Employed at Malaysian Research Universities: The Mediating Role of Employee Engagement. Journal of Entrepreneurship, Business and Economics , 11 (1), 1–41.